Effects of certain anthelmintics on the survival and reproduction of Euoniticellus intermedius (Reiche) (Coleoptera : Scarabaeidae) - Scholtz, Clarke H. (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.